The Role of Motor Vehicle Taxes in Shaping Australia's Oil Policy - Pearce, Prafula; Pinto, Dale (Taxation Institute of Australia, 2013)
Despite Australia being heavily reliant on foreign oil, with some 80% of transport fuel coming from overseas crude oil or imported fuel, it is surprising that it does not currently have a well-developed oil policy. This article makes a case for why Australia should have a well-developed oil policy and argues that the policy should recognise and respond to Australia’s high reliance on overseas crude oil or imported fuel. In this context, the article critically examines the role of motor vehicle taxes in shaping Australia’s oil policy. It is submitted that the current motor vehicle taxes in Australia are not based on sound environmental tax principles, namely the precautionary principle and the polluter-pays principle, and therefore there is a need to reform motor vehicle taxes in Australia.It is also submitted that existing motor vehicle taxes are not high enough to effect behavioural changes on motorists’ choice of motor vehicle and have little impact on the sustainability of oil as these taxes were mainly designed with the specific objective of raising revenue. Consequently, existing motor vehicle taxes have not halted the increase in demand for larger cars, including sports utility vehicles that consume more oil. Against this background, the article proposes a framework for motor vehicle tax reform and then offers some concluding comments.